Die Förderung der Kollokationskompetenz mithilfe eines Kollokationsoptimums im DaF-Unterricht - Pintye-Lukács, Erzsébet; Csatár, Péter (Linguistik Online, 2025)
Our study focuses on one of the most important areas of language education, the development of lexical competence, including collocations. When it comes to learning a foreign language, it is inevitable to encounter collocations and fixed phrases, as their use contributes to successful communication. The goal of our research is to compile a collocation optimum that can help in the teaching of collocations and in expanding the methodological tools that can be used in the development of collocation competence. Our collocation optimum is based on the analysis of six GFL textbook families (B1, B2). In the theoretical part of our study we want to emphasize the importance of teaching collocations and in the second part we would like to describe the steps of compiling the collocation optimum and the benefits of its application in the classroom.